2000
DOI: 10.1590/s0100-879x2000000800009
|View full text |Cite
|
Sign up to set email alerts
|

alpha-Tocopherol enhances tumour growth inhibition by cis-dichlorodiammine platinum (II)

Abstract: Present studies indicate that a-tocopherol enhances the efficacy of cisplatin as demonstrated by inoculation of Daltons lymphoma cells incubated with either cisplatin (5 or 10 µg/ml) alone or cisplatin + atocopherol (25 or 50 µg/ml) into C3H/He mice. Tumour cells (3 x 10 6 cells/mouse) incubated with cisplatin grow slowly in syngeneic mice as indicated by the late appearance of tumour. However, mice failed to develop tumour when inoculated with tumour cells incubated with cisplatin + a-tocopherol. When the ani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 30 publications
0
7
1
Order By: Relevance
“…Moreover, tumor growth in mice treated with the combination DDP and α‐tocopherol was similar to that observed in mice treated with DDP as a single agent. These results appear to disagree with those reported by Sarna et al ,13 who demonstrated that α‐tocopherol enhanced antitumor activity on lymphoma cells both in vitro and in vivo by increasing the influx of DDP in tumor cells. The difference between these results and our data may be due to the higher doses of α‐tocopherol employed than those used in our study.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Moreover, tumor growth in mice treated with the combination DDP and α‐tocopherol was similar to that observed in mice treated with DDP as a single agent. These results appear to disagree with those reported by Sarna et al ,13 who demonstrated that α‐tocopherol enhanced antitumor activity on lymphoma cells both in vitro and in vivo by increasing the influx of DDP in tumor cells. The difference between these results and our data may be due to the higher doses of α‐tocopherol employed than those used in our study.…”
Section: Discussioncontrasting
confidence: 99%
“…In colon cancer cells, while α‐tocopherol has very little effect on cell growth and differentiation in vitro , the redox‐inactive analogue α‐tocopheryl succinate, a strong inductor of apoptosis, shows high antitumor activity 11. Moreover, it has been reported that α‐tocopherol and α‐tocopheryl succinate enhance tumor growth inhibition in combination with DDP 12, 13, 14. Regardless of these results, α‐tocopherol, because of its antioxidants properties, might interfere with the antitumor activity of DDP, which also exerts its effect by producing ROS.…”
mentioning
confidence: 99%
“…Significant difference in response to cisplatin chemotherapy with or without combined administration of vitamin E [35]. Sarna et al found enhanced tumor growth inhibition in mice with lymphoma when the animals were receiving vitamin E and cisplatin [36].…”
Section: Discussionmentioning
confidence: 99%
“… 27 In preclinical trials in nude mice xenografted with human melanoma, there was no significant difference in response to cisplatin chemotherapy with or without combined administration of vitamin E. 28 A similar response was noted in clinical trials when comparing patients treated with cisplatin with or without vitamin E. 28 Sarna et al 29 found enhanced tumor growth inhibition in mice with lymphoma when the animals were receiving vitamin E and cisplatin. 29 A diet rich in several antioxidants, which included vitamin E, was able to slow the growth rate of lung carcinoma in mice receiving cisplatin. 30 Enhanced antitumor activity of cisplatin against neuroblastoma in mice receiving vitamin E was reported.…”
Section: Discussionmentioning
confidence: 99%